LEGAL ANALYSIS OF ABUSE OF PKPU BY DEBTORS: BETWEEN RESTRUCTURING AND DELAY OF JUSTICE - Ryzky Yan Deriza (Law Studies and Justice Journal (LAJU), 2025)
The Debt Payment Suspension (PKPU) Regulation in Indonesia, although intended as a restructuring tool, is often misused by debtors to delay payments, creatingdelay of justiceThis phenomenon is evident in the high number of PKPU (Deferred Payment for Payment) applications compared to bankruptcies, resulting in legal uncertainty, creditor losses, and declining investor confidence. This study aims to formulate an ideal legal framework to prevent PKPU abuse, balance restructuring with creditor protection, and ensure legal certainty.Using a normative juridical approach and comparative analysis with international practices (e.g.,good faith filing AS, judicial managementIn Singapore, the study found that regulatory laxity and inconsistent judicial interpretation were the main causes of abuse. The impacts included financial losses and delays in legal proceedings. Recommendations included the addition of clausesgood faith requirement, fit and proper testfor debtors, strengthening the role of supervisory judges and independent curators, and harmonizing with international bankruptcy principles. This ideal legal framework is expected to balance the restructuring function of the PKPU with justice and legal certainty for all parties.